From Leisure to Legacy: The Role of Staycations in Strengthening Cultural Identity in Qatar - Abdallah, Ali (Journal of Posthumanism, 2025)
This study investigates the cultural significance of staycations among Qatari nationals, positioning domestic tourism not merely as a substitute for international travel, but as a culturally meaningful practice that contributes to national identity, social cohesion, and intergenerational continuity. While staycations gained prominence globally during the COVID-19 pandemic, in Qatar, they have evolved into intentional acts of cultural engagement that align with broader state narratives, particularly those underpinning Qatar National Vision 2030. Drawing on a mixed-methods design, this research combines survey data from 152 Qatari respondents with ten in-depth qualitative interviews involving residents, tourism professionals, and cultural stakeholders. Quantitative findings reveal strong correlations between staycation frequency, cultural pride, place attachment, and family involvement. Respondents expressed high levels of agreement with statements linking local travel to emotional well-being, community trust, and a deeper connection to Qatari heritage. The qualitative data enrich these trends, unveiling how staycations function as modern cultural rituals, reaffirming traditional practices such as storytelling, food preparation, and collective memory-making. New emergent themes, such as “tourism as civic participation,” further highlight how staycations are seen by some as soft expressions of patriotism and national responsibility. The study draws upon Cultural Capital Theory, Place Attachment Theory, and Social Cohesion frameworks to interpret how domestic tourism practices reinforce national belonging in a rapidly globalising society. By framing staycations as vehicles for cultural continuity and civic engagement, the study expands current understandings of leisure in the Gulf context and addresses a notable gap in tourism scholarship. It concludes with practical recommendations for policymakers and cultural institutions, calling for tourism planning that goes beyond economic indicators to include cultural value metrics, generational inclusivity, and identity-building objectives.